USING CENTER OF GRAVITY EQUATION FOR MICA AND SMECTITE IN EVALUATION OF K-STATUS IN SOME SOILS OF IRAQI KURDISTAN REGION - B.O. Al- Jaff (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Ten soil sites were chosen in Iraqi Kurdistan region, included the governorates of (Sulaimani, Arbil, and Duhok). These soils were characterized by their similarity in texture, parent material, topography, climatic conditions, and equal rainfall, in order to study the use of the center of gravity equation and mineralogical properties in evaluating the state of potassium in soils of different plant coverage (Forest, crops, and uncultivated soils). Results showed there was a variation in the values of calculated center of gravity for studied soil samples, which ranged between (0.83 – 1.63). The variation in these values was attributed to the variation between the studied soils in their ability for potassium supplying, depending on the nature of plant coverage, soil texture, mineralogical properties, and the intensity of weathering. The X-ray analyses of clay fraction revealed, that the forest soils were content a high amount of 2:1 expandable clay minerals, mica, and interstratified minerals, while the crop and uncultivated soils were contained a low amount of interstratified minerals. The distribution of minerals in studied soils, suggested the transformation of mica into 2:1 expandable clay minerals in forest soils, and no or minimal transformation of mica into 2:1 expandable clay minerals in crop and uncultivated soils.